Sudang Lepet: Jejak Sejarah Home Industri Kuliner Tradisional di Desa Sangsit - Ketut Diah Darmiasih; I Wayan Putra Yasa; Desak Made Oka Purnawati (Universitas Veteran Bangun Nusantara, 2026)
This study aims to examine the historical development of the Sudang Lepet home industry in Sangsit Village, Sawan District, Buleleng Regency. This Sudang Lepet home industry is a traditional culinary business that has been operating since 1992 and has become part of the local community's cultural identity. This study employed historical research methods including heuristics, source criticism, interpretation, and historiography. Data sources were obtained through interviews with business owners, field observations, documentation, and relevant literature studies. The results indicate that the history of the Sudang Lepet home industry began as a small-scale home business, then was managed and passed down through generations within the family. Its development was influenced by the economic needs of the community and efforts to preserve the traditional food of Sangsit Village. Although the economic impact has not significantly impacted the entire village community, this home industry plays a crucial role in preserving the local culinary heritage and fostering cultural pride. In addition, Sudang Lepet has become a local identity that strengthens traditional values in the midst of modernization. Thus, the history of the Sudang Lepet home industry not only describes the dynamics of the village community's economic efforts, but also reflects efforts to preserve local culture that has historical and educational value.